Predictive value of common clinical and laboratory parameters in predicting response to Anti thyroid drug therapy in Graves’ Hyperthyroidism – A prospective study - Gopalakrishnan, Sripathy; Chugh, Pradeep; Chhillar, Mitrabasu; Chhillar, Neelam; Sankar, Rajan (International Journal of Medicine, 2013)
Purpose: Graves’ hyperthyroidism (GH) is commonly treated by antithyroid drugs (ATD). This study was undertaken to identify those clinical factors that could predict sustained remission with ATD so as to avoid unwanted therapy. Approach: Subjects (n=134) diagnosed with GH were consecutively recruited. Carbimazole was administered for 18 months as per titration regimen and subsequently followed up for upto 1 month to detect relapse of thyrotoxicosis. Results: In final analysis of 115 subjects, 61 remained in remission while thyrotoxicosis recurred in 54 subjects during followup. Parameters associated with remission for at least 6 months were : smaller goiter, lower free triiodothyronine (FT3 ) values at onset and euthyroidism in response to ATD within 3 – 6 months. Conclusions: 50% of patients went into remission with carbimazole therapy for 18 months. Subjects who fail to achieve euthyroidism with 6 months of ATD should be offered radioiodine or surgery.